Nanofiltration of multi-solute systems: Solute interactions and theory. - Stephen John Mandale (2005)
From the outset, membrane researchers have studied the behaviour and governing processes of membrane separations. Theoretical representation of membrane transport systems is central to membrane research and the most recent investigations have considered single and binary solute systems of charged and uncharged species. A gap in the research was detected with respect to systems of combined charged (dissociated) and uncharged (non-dissociated) species. Thus these systems were explored from both a practical-experimental and theoretical perspective. The result of experimental investigation into combined systems of charged/uncharged solutes, was an observation of negative rejections for uncharged solutes in the presence of high salt concentrations. This is a phenomenon that was not observed elsewhere and in general the rejection of uncharged solutes was attributed to steric factors hence a direct interaction between salts and neutral solutes was not suggested. The reliability of the negative rejection observations was established through a discussion of experimental error and a consideration of concentration polarisation. It was found that the error was negligible and that the measured negative rejections (approximately -10% in some cases) were not attributable to variation in the results caused by external influences. An analysis of concentration polarisation only served to amplify the negative rejection observed, since real rejection (that at the membrane surface) exhibited greater negativity than the observed rejection. The observed phenomenon was discussed with respect to current forms of membrane transport theories. The semi-black box technique proposed by Spiegler and Kedem and later modified by Van der Bruggen and co-workers was found to provide a reasonable fit of the experimental data where valance was taken to be a non-integer fitting parameter. Errors in the Fortran implementation of the Bowen and Welfoot development of the Donnan Steric Partitioning Model (DSPM) prevented this transport theorem from being explored in relation to the measured phenomenon. Thus it was a recommendation of this work that this theory should be considered in more depth.